Entre ensayo, poesía y cine: la construcción discursiva de la villa miseria en la obra de César González. - Salomé Dahan (Cuadernos LIRICO)
César González was born in 1989 in the villa miseria Carlos Gardel, outside Buenos Aires. At the age of sixteen, he was incarcerated in various prisons for minors, where he had access to the classics of philosophy, literature and cinema. In the poems of his first collection La venganza del cordero atado (2010), as well as in the films of the villera tetralogy and the essays of El fetichismo de la marginalidad (2021) he explores the aesthetic possibilities of the villas miseria. His work develops an original language that transforms traditional perspectives on space.